The Influence of Healthy, Smart, and Drug-Free Achievement Education on Students’ Character Education in Collaboration with the National Narcotics Agency (BNN) - Yuris Indria Persada; Aprilia Putri Wulandari; Fidela Faustina; Nuravissa Digna Sari (Jurnal Pendidikan Vokasi Indonesia, 2026)
This study aims to examine the influence of the educational program themed “Healthy, Smart, and Achieving Without Drugs” in collaboration with the National Narcotics Agency (BNN) on the character education of elementary school students. The research was conducted using a pre-experimental design with a one-group pretest–posttest approach involving third and fourth-grade students in Tulungagung, East Java. Data were collected through pretests and posttests to measure students’ knowledge and understanding of character values related to healthy living and drug prevention. The results of the statistical analysis indicated a significant difference between the pretest and posttest scores, with a significance value of 0.000 (<0.05). These findings reveal that the educational intervention has a positive and significant effect on improving students’ understanding of character values. The program not only increased awareness of the dangers of drugs but also motivated students to achieve through positive behavior and healthy lifestyles. The collaboration between schools and BNN proved to be an effective early preventive measure against drug abuse while strengthening students’ character education. This study concludes that sustainable cooperation between educational institutions and BNN is essential for fostering character values in students. It is recommended that schools, teachers, parents, and communities work together to create a supportive environment that promotes healthy, intelligent, and high-achieving student development.